Fatigue and harmonic analysis of a diesel engine Crankshaft using ANSYS - Muhammad, Aisha; Ali, Mohammed A. H.; Shanono, Ibrahim Haruna (Springer, Singapore, 2019)
The performance and reliability of an internal combustion engine depend on the robustness of the engine crankshaft as it is one of its important moving component. An internal combustion engine is affected by the vibration activities of a crankshaft. This vibration performance is hard to determine due to the complex nature of the crankshaft. In the past, the stress in a crankshaft is calculated using the methods of beam and frame model. To avoid failure of an engine crankshaft, calculation of the crankshaft strength becomes an importance component. In this paper, fatigue, failure and harmonic response analysis of an internal combustion engine by Finite Element method (FEM) using ANSYS workbench were carried out. The analysis is carried out in ANSYS static struc-tural, mechanical solver on a structural steel material. Result from the transient analysis indicates presence of stress at the crankpin journals and with the ap-pearance of deformation at its crank nose. The failure analysis safety factor is high in the Gerber theory being a structural steel material. Increase in the order number also increases the harmonic response frequencies.